2023
DOI: 10.3390/nu15071732
|View full text |Cite
|
Sign up to set email alerts
|

Renal-Protective Roles of Lipoic Acid in Kidney Disease

Abstract: The kidney is a crucial organ that eliminates metabolic waste and reabsorbs nutritious elements. It also participates in the regulation of blood pressure, maintenance of electrolyte balance and blood pH homeostasis, as well as erythropoiesis and vitamin D maturation. Due to such a heavy workload, the kidney is an energy-demanding organ and is constantly exposed to endogenous and exogenous insults, leading to the development of either acute kidney injury (AKI) or chronic kidney disease (CKD). Nevertheless, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 180 publications
0
1
0
Order By: Relevance
“…ALA is a disulfide compound synthesized from octanoic acid in the mitochondria; it may also be found in the human diet, such as in meat, potatoes, and fresh egg yolk. ALA is well known for its powerful antioxidative effects and is commonly used in the treatment of chronic inflammatory diseases associated with high levels of oxidative stress, such as diabetic polyneuropathy, Alzheimer's disease, and renal diseases [35][36][37]. A growing body of evidence has demonstrated that ALA can also suppress the growth, migration, and invasion of various cancer cell lines, although the underlying mechanisms of action of ALA are complex and vary according to the type of cancer cell [10][11][12][13][16][17][18][19][20][21][22][23][24][25][26][27]38,39].…”
Section: Discussionmentioning
confidence: 99%
“…ALA is a disulfide compound synthesized from octanoic acid in the mitochondria; it may also be found in the human diet, such as in meat, potatoes, and fresh egg yolk. ALA is well known for its powerful antioxidative effects and is commonly used in the treatment of chronic inflammatory diseases associated with high levels of oxidative stress, such as diabetic polyneuropathy, Alzheimer's disease, and renal diseases [35][36][37]. A growing body of evidence has demonstrated that ALA can also suppress the growth, migration, and invasion of various cancer cell lines, although the underlying mechanisms of action of ALA are complex and vary according to the type of cancer cell [10][11][12][13][16][17][18][19][20][21][22][23][24][25][26][27]38,39].…”
Section: Discussionmentioning
confidence: 99%
“…α-Lipoic acid (α-LA) (1,2-dithiolane-3-pentanoic acid or thioctic acid) is a natural dithiol that is enzymatically synthesized in plants, animals and humans and found in meat, the heart, kidneys and liver, fruits and vegetables [150]. α-LA is a powerful antioxidant due to its redox properties and its ability to directly capture ROS [151]. The common mechanisms of the protective action of α-LA for the kidneys, which include reducing oxidative damage, increasing antioxidant capacity, countering inflammation, softening renal fibrosis and weakening nephron cell death, have recently been identified [152].…”
Section: α-Lipoic Acidmentioning
confidence: 99%
“…The global prevalence of kidney diseases exceeds 10% [1]. As a vital organ, the kidney functions as the maintenance of electrolyte balance, the stability of blood pH, removal of metabolic waste, and reabsorption of nutrients and minerals for the body [2]. Additionally, the kidney also regulates blood pressure, vitamin D maturation, and erythropoiesis.…”
Section: Introductionmentioning
confidence: 99%